THE PECULIARITIES OF THE MENSTRUAL CYCLE AT FEMALE MILITARY PERSONNEL THAT SUFFERED CONTUSION IN HOSTILITIES (World Science, 2021)
The article presents an analysis of literature data and the results of our own retrospective studies of the characteristics of the menstrual cycle in female combatants who have undergone concussion. Clinical and anamnestic factors have been identified that negatively affect the menstrual function of women of reproductive age, who received contusions during hostilities. The relationship between the state of mental health of women and menstrual irregularities has been established. Aim: to identify and evaluate changes in the menstrual function of women - veterans of reproductive age. Also, to establish the relationship between menstrual irregularities in women - veterans of reproductive age who have undergone contusion, and the state of their somatic and mental health.Materials and method: The research was conducted at the Department of Obstetrics, Gynecology and Reproductology of the National University of Health of Ukraine named after P.L. Shupika. To achieve this goal, a comprehensive clinical and laboratory examination was performed in 567 women of reproductive age (main group and comparison group) who participated in hostilities and suffered contusions, the average age of the subjects was 27.08 ± 4.23 years.The period of stay in the combat zone is 29.34 ± 9.21 months, the time from the moment of receiving a mild traumatic brain injury (contusion) is 18.8 ± 9.2 months. Group I - 399 fertile women who suffered contusions during the fighting with PKS. Group II - 168 women of childbearing age who suffered contusions during hostilities without PKS (mean age 32.21 ± 7.32 years).Results: The results of the studies revealed statistically significant deviations in the characteristics of the menstrual cycle of women who participated in hostilities who were injured with PKS, compared with women without PKS. It has been proven that women-viskovosluzhvits more often develop menstrual irregularities, namely a decrease or increase in the number, lengthening or shortening of the menstrual cycle by 7 days. Taking into account the revealed menstrual irregularities in the women under study, it can be argued that the detected changes are due to the influence of both craniocerebral trauma and stress factors associated with military service. This justifies the need to develop a program for monitoring and supporting the reproductive health of women-viyskovoservices, as well as medical and psychological rehabilitation of veterans, aimed at their full adaptation to a peaceful life.